Human-Computer Interaction: Trends, Research, Future - Kamill Akhmetov (Foresight and STI Governance)
With information and communication technologies becoming an essential part of human life, the very nature of relations between human and computers is changing. Technologies are aimed at augmenting certain human values, but they may contradict with other values thus having adverse implications for quality of life. Is it possible to preserve key values in the face of such transformations? The solution of this vital question largely depends on research and development in Human-Computer Interaction (HCI) — an interdisciplinary field that has gained rapid development in recent decades.